STRATEGI MANAJEMEN PT NEO GLOBAL ERA (Gojek) BANJARMASIN - Ni Nyoman Suarniki; Tri Cicik Wijayanti (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2019)
Abstract, The research objective is to determine the competitive strategy adopted by PT Neo Global Era (Gojek) Banjarmasin. The research population was all drivers gojek, with a sample of 31 people with randomly simple. Data obtained from interviews, questionnaires and observations, then analyzed using descriptive approaches. The results of this research indicate that the competitive strategy adopted by PT Neo Global Era (Gojek) Banjarmasin in maintaining and increasing the number of drivers is to provide assistance in the appeal process (if affected by sanctions), provide tranning (service and socialization of regulations) the results are less satisfying. Promotion of social media (FB and WA) results are less satisfying drivers, invitations to join or partner the results are satisfactory, making conversation groups the results are less satisfactory, Direction for smart work results do not yet exist, solicitation to consumers to fill gopay balance results are not satisfactory.